MODEL TAJUK TERKENA CAHAYA JATI PLUS PERHUTANI ASAL KEBUN BENIH KLON PADA UMUR 6 SAMPAI 11 TAHUN DI KPH MADIUN - , WIWIK NUR HANDAYANI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Increasing productivity of teak plantation by Perhutani is done by providing high genetic value named Perhutaniâs Teak Plus Plantation which are planted from Clonal Seed Orchad. Forest stand dynamics not only in the form of diameter and height, but also the tree crown. Tree crown plays an important role in the productivity of the tree. This research is needed to provide reference for Perhutaniâs Teak Plus Plantation growth. The aim of this study is to determine the lighted crown model and the estimated lighted crown volume for Perhutaniâs Teak Plus Plantation aged 6 to 11 years in Madiun Forest District. Lighted crown model use modelled from measurement of tree diameter, tree height, maximum crown radius, crown base and maximal crown height for dominant trees in each plot sampled plants with good growth. The data was processed to find out the crown length, lighted crown length and shaded crown length to obtain the mean value of each age. Furthermore modeling presented by Pretzcshâs approach, the lighted crown volume was estimated by rotary volume objects. The results showed that Perhutaniâs Teak Plus Plantation lighted crown models described to parabolic form with the equation be as follow Rl6=1,02*hl6 0,33, Rl7=1,19*hl7 0,33, Rl8=1,23*hl8 0,33, Rl9=1,28*hl9 0,33, Rl10=1,17* hl10 0,33, Rl11=1,32*hl11 0,33, in which Rl is the radius of lighted crown section (m) and hl is crown height lighted crown section (m). While the estimated lighted crown volume is 10,5653 m3, 20,8365 m3, 42,3296 m3, 46,8301 m3, 46,6000 m3 and 58,4915 m3 for aged 6 to 11 years respectively.